Lateral abutment pressure distribution and evolution in wide pillars under the first mining effect - Zhang, Zhen; Li, Zhen; Xu, Gang; Gao, Xiaojin; Liu, Qianjin; Li, Zhengjie; Liu, Jiachen (International journal of mining science and technology, 2023)
The wide pillars are generally popular due to the high productivity and efficiency in Northwest China. The distribution of lateral abutment pressure in coal pillars is important for mining safety. To reveal the effect of the first mining on the lateral abutment pressure distribution and evolution in wide pillars, an in-situ experiment, theoretical analysis and numerical simulation were performed. First, the field monitoring of lateral abutment pressure was conducted from the perspective of time and space in the Chahasu Coal Mine, Huangling No. 2 Coal Mine and Lingdong Coal Mine during the first mining. Based on the field monitoring stress, a theoretical model was proposed to reveal the lateral abutment pressure distribution. The methodology was demonstrated through a case study. Aiming at the distribution mechanism, a numerical experiment was conducted through the finite-discrete element method (FDEM). Last, field observations of borehole fractures were performed to further study the damage distribution. In addition, two types of lateral abutment pressure evolution with mining advance were discussed. Suggestions on the stress monitoring layout were proposed as well. The results could provide foundations for strata control and disaster prevention in wide pillars in underground coal mines.